Harman and isoquinoline alkaloids from Litsea petioluta Hk.f (Lauraceae) - Omar, Hanita; Nafiah, Mohd Azlan; Mukhtar, Mat Ropi; Awang, Khalijah; A. Hadi, Hamid (Malaysian Journal of Science, 2010)
A phytochemical investigation on the alkaloids of the barks of Litsea petiolata Hk.f obtained from Reserved Forest Teloi, Sik, Kedah has resulted in the isolation of 5 compounds namely harman or aribine (1) , norharman (2) , reticuline (3) , isoboldine (4) and thalifoline (5) . Their structures were established through the spectroscopic techniques such as UV, IR, GC-MS, 1D and 2D-NMR.